Poetry Genre in Secondary School Turkish Lesson Teaching Programs (1924-2019) - Ekinci, Muzaffer; Demirel, Sener (Salim DURUKOĞLU, 2023)
Turkish Curricula are constantly renewed in line with the needs of the age and the country and are organized in a way to respond to the conditions of the day. From the proclamation of the Republic to the present day, Turkish Language Teaching Programs have also undergone changes within the framework of these needs. The element most affected by this change and transformation has been the texts selected for textbooks. In this study, the poetry genre in the secondary school Turkish Lesson Teaching Programs (1924-2019) was examined. The original copies of the relevant programs were accessed and the programs were examined according to chronological history. In the study, document analysis method was used in qualitative design among data collection techniques. Content analysis technique was used to analyze the data. As a result of the content analysis, it was concluded that poetry was given less space in the 1924-1981 Turkish Language Teaching Programs compared to other genres, and it was aimed to spread the standard language by eliminating the pronunciation problems of the student through poetry texts. In addition, it is aimed to increase the student's ability to address and to give the student aesthetic sensitivity. 2006 and later Turkish Language Teaching Programs aim to further develop the student's grammar and four basic language skills with activities related to the poetry genre and poetry in addition to the acquisitions to be gained in the previous programs.

Türkçe Dersi Öğretim Programları, çağın ve ülkenin ihtiyaçları doğrultusunda sürekli yenilenerek günün şartlarına cevap verecek şekilde düzenlenmektedir. Cumhuriyetin ilanından günümüze kadar söz konusu ihtiyaçlar çerçevesinde Türkçe Dersi Öğretim Programları da değişime uğramıştır. Bu değişim ve dönüşümden en fazla etkilenen unsur ders kitaplarına seçilen metinler olmuştur. Bu çalışmada ortaokul Türkçe Dersi Öğretim Programlarında (1924-2019) yer alan şiir türü irdelenmiştir. İlgili programların orijinal nüshalarına ulaşılarak programlar kronolojik tarihe göre incelenmiştir. Çalışmada veri toplama tekniklerinden nitel desende doküman analizi yöntemi kullanılmıştır. Verilerin analizinde ise içerik analizi tekniğinden yararlanılmıştır. Yapılan içerik analizi sonucunda 1924-1981 Türkçe Dersi Öğretim Programlarında şiir türüne diğer türlere nazaran daha az yer verildiği, şiir metinleri aracılıyla öğrencinin telaffuz problemlerini ortadan kaldırarak standart dilin yaygınlaştırılması hedeflenmiştir. Bunun yanında öğrencinin hitap kabiliyetinin artırılması ve öğrenciye estetik duyarlılık kazandırma hedeflenmiştir. 2006 ve sonrasında hazırlanan Türkçe Öğretim Programları önceki programlarda kazandırılması gereken kazanımların yanında şiir türüne, şiir ile ilgili etkinlikler ile öğrencinin dil bilgisi ve dört temel dil becerisinin daha da geliştirilmesini hedeflemişlerdir.
Ortaokul Türkçe Dersi Öğretim Programlarında (1924-2019) Şiir Türü
Keywords: Turkish Education; Türkçe Eğitimi